A Human Being as a Part of the Security Control System at the Airport. (2016) - Skorupski, Jacek; Uchroński, Piotr
Abstract: The passenger and baggage security in airport screening system is one of the most important factors that determine air transport safety and security. It prevents objects and materials that could be used to commit an act of unlawful interference from being placed on board an aircraft. The security screening system consists of x-ray screening devices, walk-through metal detectors and specialised software. However, a key element of the security screening system is the human – the security screener (SSc). The equipment and software helps the screener to find prohibited items, but also detects and records his/her errors. The whole security control point (SCP) can be regarded as a complex socio-technical system. It's effectiveness is dependent, inter alia, on the type of x-ray devices used, a variant of SCP organisation or the technical condition of the equipment, but mainly on the quality of the security screeners' work. Special attention is paid to the types of errors and their frequency. We analyze the quantitative relationships between types of errors and also between the frequency of errors and the frequency of virtual threat images projection (TIP). This last technology is a kind of intelligent support system and at the same time verifies the screener's work. The study was based on measurements under real conditions at the Katowice-Pyrzowice International Airport. In the framework of this research two basic types of errors made by SSc were identified. The results show that the number of errors is dependent from the frequency of the stimulus, represented by TIP images. As a result, it was possible to determine the recommended frequency of threat images projections. The study is supplemented by a comparison of the screeners' effectiveness in laboratory conditions against real conditions, while working at the security control point.